Representative farms economic outlook for the December 2013 FAPRI/AFPC Baseline - James W. Richardson; Joe L. Outlaw; George M. Knapek; J. Marc Raulston; Brian K. Herbst; David P. Anderson; Steven L. Klose (Texas A&M University, The Agricultural & Food Policy Center (AFPC), 2013)
The Agricultural and Food Policy Center (AFPC) at Texas A&M University develops and maintains data to simulate 98 representative crop, dairy, and livestock operations in major production areas in 28 states. The chief purpose of this analysis is to project the economic viability of those farms by region and commodity for 2013 through 2018. The data necessary to simulate the economic activity of these operations is developed through ongoing cooperation with panels of agricultural producers in selected states. The Food and Agricultural Policy Research Institute (FAPRI) provided projected prices, policy variables, and input inflation rates in their December 2013 Baseline. Under the December 2013 Baseline, 46 of the 66 crop farms are considered in good liquidity condition (less than a 25 percent chance of negative ending cash by 2018). Five crop farms have between a 25 percent and a 50 percent likelihood of negative ending cash, and the remaining 15 crop farms have greater than a 50 percent chance of negative ending cash. Additionally, 58 of the 66 crop farms are considered in good equity position (less than a 25 percent chance of decreasing real net worth during the study period). Five crop farms have between a 25 percent and 50 percent likelihood of losing real net worth, and only three crop farms have greater than a 50 percent probability of decreasing real net worth. The following discussion provides an overall evaluation by commodity considering both liquidity and equity measures. * FEEDGRAIN FARMS: Eighteen of the 24 feedgrain farms are in good overall financial condition. Five are classified in marginal condition, and one is in poor condition. * WHEAT FARMS: Nine representative wheat farms are classified in good overall financial condition; two are in marginal condition * COTTON FARMS: Twelve of the 17 cotton farms are classified in good condition, three are in marginal condition, and two are in poor condition. * RICE FARMS: Seven of the 14 rice farms are projected to be in good financial condition, three are in marginal condition, and four are in poor condition. * DAIRY FARMS: Eight of the 21 dairies are in good overall financial condition. Eight are also classified in marginal condition; five are in poor condition. * BEEF CATTLE RANCHES: Seven of the 11 cattle ranches are classified in good financial condition, three are in marginal condition, and one is projected to be in poor condition.
Keywords: 330